2005
DOI: 10.1093/eurheartj/ehi187
|View full text |Cite
|
Sign up to set email alerts
|

TIMI, PURSUIT, and GRACE risk scores: sustained prognostic value and interaction with revascularization in NSTE‐ACS

Abstract: The RSs studied demonstrated a good predictive accuracy for death or MI at 1 year and enabled the identification of high-risk subsets of patients who will benefit most from myocardial revascularization performed during initial hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
257
0
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(286 citation statements)
references
References 20 publications
15
257
0
14
Order By: Relevance
“…25 A comparison of TIMI, GRACE and PURSUIT scores concluded that all three risk scores demonstrated "good predictive accuracy for death or myocardial infarction at 1 year, and enabled the identification of high-risk subsets of patients who will benefit most from myocardial revascularization performed during initial hospital stay." 26 So why did these risk scores fare poorly in our study of patients who presented to the ED with potential ACS? Firstly, we should note that the ROC areas of 0.757 and 0.728 cited above do not suggest excellent predictive value.…”
Section: Discussionmentioning
confidence: 92%
“…25 A comparison of TIMI, GRACE and PURSUIT scores concluded that all three risk scores demonstrated "good predictive accuracy for death or myocardial infarction at 1 year, and enabled the identification of high-risk subsets of patients who will benefit most from myocardial revascularization performed during initial hospital stay." 26 So why did these risk scores fare poorly in our study of patients who presented to the ED with potential ACS? Firstly, we should note that the ROC areas of 0.757 and 0.728 cited above do not suggest excellent predictive value.…”
Section: Discussionmentioning
confidence: 92%
“…Due to its high predictive accuracy it is nowadays the most widely used risk score in ACS. 13 More recently, both the Mayo Clinic and the National Cardiovascular Data Registry developed risk scores for patients undergoing coronary angioplasty. 2,3 Both scores included patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…7 They have looked at short-term as well as long-term mortality. They have clearly demonstrated that GRACE score was the best in predicting the risk of death or MI at 1 year after admission.…”
Section: Grace Scoring Systemmentioning
confidence: 99%